Emerging middle powers (mikta) in global political economy: Preferences, capabilities, and their limitations - (:unkn) unknown (Palgrave Macmillan, 2020)
Today’s emerging order encompasses fundamental clash of norms of political economy in the sense that the key elements of the so-called Beijing Consensus seem to challenge the liberal developmental and democratic norms associated with Western-based norms of the Washington Consensus. This paper attempts to comparatively analyze emerging middle powers (MIKTA) material capabilities and ideational preferences in the changing global political economy dynamics throughout 2000s in order to depict any meaningful evidence illustrating enhanced cooperation under this minilateral initiative. To this aim, drawing on the emerging middle power concept, this study will compare and contrast the (1) material capabilities, (2) ideational roles, and (3) MIKTA perceptions of each member countries in the 2010s in a time of clashing norms of global political economy. The paper concludes that, among others, so far, sustainable development issues have played a relatively prominent role in MIKTA’s general rhetoric. However, MIKTA, for the time being, is far from being an influential and more effective model of global governance for middle powers due to various domestic political problems among its members diverting their attention away from the institutional empowerment of cooperation within this informal partnership. © 2020, The Author(s).
Keywords: Emerging middle powers; Global political economy; Ideational preferences; Material capabilities; MIKTA